Pelatihan Pencatatan Akuntansi Berbasis Aplikasi Fintech Bagi Pelaku UMKM Penjual Pinang Mama Mama Papua di Kelurahan Entrop Kota Jayapura - Asnawi, Meinarni; Sesa, Pascalina V.S.; Rofingatun, Siti; Pahabol, Yeniva (The Community Engagement Journal, 2024)
Micro, small and medium enterprises (MSMEs) are one of the economic drivers that play an important role in the Indonesian economy. One of the common problems faced by MSME players is financial, such as a lack of understanding and awareness of the importance of financial planning and management (Raharjo et al., 2022). Often viewed as a complex concept, financial management is an important driver of growth for MSMEs. By engaging in financial planning and management, MSME owners can clearly understand the financial health of their business over a certain period. However, some MSME players still consider financial management to be scary and insignificant. The community service program (PKM) is a proactive initiative to empower MSMEs, especially those selling areca nut in Entrop Village, Jayapura City, to master finances and utilize financial technology. Program activities, which include knowledge sharing and hands-on training in financial management and the use of financial technology, are designed to equip MSMEs with the tools they need to thrive. The conclusion that can be drawn from the Fintech Application-Based Accounting Recording Training for Papuan Sirih Selling MSMEs in Entrop Village, Jayapura City, is to increase the knowledge and understanding of Papuan Sirih Selling MSMEs to grow and be able to record business finances and support the sustainability of their business well.